Effects of Ga on the structural, mechanical and electronic properties of β-Ti-45Nb alloy by experiments and ab initio calculations - Alberta, Ludovico Andrea; Fortouna, Yannick; Vishnu, Jithin; Pilz, Stefan; Gebert, Annett; Lekka, Christina; Nielsch, Kornelius; Calin, Mariana (Journal of the Mechanical Behavior of Biomedical Materials, 2023)
This work aims to investigate the structural, mechanical and electronic properties of four novel β-type (100-x)(Ti–45Nb)-xGa alloys (x = 2, 4, 6, 8 wt%) for implant applications by means of experimental and theoretical (ab initio) methods. All alloys retain the bcc β phase in the solution-treated and quenched state while the lattice parameter decreases with increase in Ga content. This is due to its smaller atomic radius compared to Ti and Nb, in line with the present density functional theory (DFT) calculations. Tensile and microhardness tests indicate a clear strengthening effect with increasing Ga content, with yield strengths in the range 551 ÷ 681 MPa and microhardness in the range 174 ÷ 232 HV0.1, mainly attributed to grain refinement and solid solution strengthening. Ga also positively affects ductility, with a maximum value of tensile strain at fracture of 32%. Non-destructive ultrasonic measurements and DFT calculations reveal that the bulk modulus is unaffected by the Ga presence. This phenomenon might be due to the fact that Ga introduced bonding and anti-bonding electron low energy states which balance the average bond strength among the atoms in the metallic matrix. Nevertheless, the introduction of new Ga–Ti super sp-like bonding orbitals along the [110] and [−110] directions in the Ga neighborhood could explain the increase of the Young's modulus upon Ga addition (73 ÷ 82.5 GPa) that was found experimentally in the present work. Hence, Ga addition to Ti–45Nb leads to a suitable balance between increased strength and low Young's modulus.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Ab initio; Beta-Ti alloys; Biomaterial; Gallium; Implant applications; Mechanical properties